2008
DOI: 10.1042/cs20070462
|View full text |Cite
|
Sign up to set email alerts
|

Role of PPARγ in renoprotection in Type 2 diabetes: molecular mechanisms and therapeutic potential

Abstract: DN (diabetic nephropathy) is a chronic disease characterized by proteinuria, glomerular hypertrophy, decreased glomerular filtration and renal fibrosis with loss of renal function. DN is the leading cause of ESRD (end-stage renal disease), accounting for millions of deaths worldwide. TZDs (thiazolidinediones) are synthetic ligands of PPARgamma (peroxisome-proliferator-activated receptor gamma), which is involved in many important physiological processes, including adipose differentiation, lipid and glucose met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 128 publications
4
32
0
Order By: Relevance
“…Consequently, whether or not systemic blood pressure is correlated with the renoprotective effect of PGZ is a significant issue. The effect of TZD on blood pressure is still controversial, dependent on individual reports [29]. In the present study, it was clearly shown that systemic blood pressure was not affected by the administration of PGZ for 2 weeks.…”
Section: Discussionsupporting
confidence: 55%
“…Consequently, whether or not systemic blood pressure is correlated with the renoprotective effect of PGZ is a significant issue. The effect of TZD on blood pressure is still controversial, dependent on individual reports [29]. In the present study, it was clearly shown that systemic blood pressure was not affected by the administration of PGZ for 2 weeks.…”
Section: Discussionsupporting
confidence: 55%
“…These findings are potentially interesting in terms of pathophysiology, since TZDs have been reported to expand body fluid volume through PPARγ stimulation of the epithelial Na + channel-mediated renal salt absorption [32]. Reno-protective effects of PPARγ ligands on type 2 diabetic patients with nephropathy, especially their effects on reducing urinary albumin, have recently been reported [33]. Additionally, similar effects have been observed in animal experiments using various rodent models of type 2 diabetes [33].…”
Section: Effects Of Pparγ On Atherosclerosissupporting
confidence: 56%
“…Reno-protective effects of PPARγ ligands on type 2 diabetic patients with nephropathy, especially their effects on reducing urinary albumin, have recently been reported [33]. Additionally, similar effects have been observed in animal experiments using various rodent models of type 2 diabetes [33]. The mechanisms by which PPARγ ligands reduce urinary albumin remain unclear.…”
Section: Effects Of Pparγ On Atherosclerosismentioning
confidence: 71%
“…Sobel et al (15) reported that, in BARI 2D subjects, IS as opposed to IP treatment led to changes in biomarker profiles that were indicative of a profibrinolytic, antithrombotic, and antiinflammatory state. Peroxisome proliferator-activated receptors are widely expressed in the kidney, and peroxisome proliferator-activated receptor gamma agonists have renoprotective effects in experimental models of diabetic kidney disease (16,17). Administration of TZDs to insulin-deficient and -resistant diabetic rats ameliorated albuminuria and histologic hallmarks of diabetic nephropathy (18,19).…”
Section: Discussionmentioning
confidence: 99%